The hepatocyte traffic network in the human hepatitis A virus biological cycle from an evolutionary perspective - Albert Carcereny; Alba Arrebola; Gemma Chavarria-Miró; Montserrat de Castellarnau; Cristina Fuentes; David Garcia-Pedemonte; Adán Martínez-Velázquez; Enric Ribes; Albert Bosch; Susana Guix; Maria Isabel Costafreda; Rosa M. Pintó (Communications Biology)
Abstract Hepatitis A virus (HAV) egresses from hepatocytes cloaked in exosomes (eHAV). However, the traffic network used for its release from polarized hepatocytes is not completely understood. We propose that eHAV biogenesis may follow not only an ESCRT-mediated pathway but also the syndecan-syntenin-ALIX pathway. The Bro1 and the V domains of ALIX bind to the pX extension of VP1 and the VP2-late domains of the unmature capsid, respectively. A Serine-to-Glycine replacement at position 134 of VP2, closely located with the first late domain, facilitates the interaction with ALIX promoting the syndecan-syntenin-ALIX pathway and improving the basolateral egress, preferentially using RAB35. This replacement is conserved in hepatoviruses infecting a wide range of mammalian species, but not in hepatoviruses infecting chimpanzees and humans. An inefficient basolateral egress could be a strategy to escape the antiviral cellular response in apes.